CRIMINOLOGY STUDENTS’ ATITTUDE TOWARDS THE USE OF INSTRUCTIONAL MATERIALS - Lim, Johnnie Jada (PEOPLE: International Journal of Social Sciences, 2015)
Using experimental research, this study determined whether different teaching approaches influence students’ interest to learn. Specifically, this study examined whether or not using instructional materials could help improve students’ performance in Technical Report Writing/Police Report Writing course. This study also aimed to determine whether or not the students’ attitude towards police report writing and communication skills through the teaching approach used in this experiment was positive. Forty-six second year Criminology students of SSC-R were the respondents in this study. Thirty-six of them belonged to Section A, and ten of them belonged to Section B. The results showed that although there’s a difference in performance between students using instructional materials and students not using instructional materials, the result was insignificant. In addition, the students’ attitude toward police report writing and communication skills in both sections was positive and significantly different. The findings of this study provided explanation on the use of instructional materials and the use of different teaching approaches in teaching Technical Report Writing/Police Report Writing to Criminology students.